Teaching methods through the eyes of Bulgarian students from three generations - Dragomir Iliev; Daniela Ilieva; Zhelyo Zhelev (Tuning Journal for Higher Education)
This article aims to identify the attitudes of different generations regarding certain aspects of the teaching approaches used during the education of economic disciplines. The analysis primarily draws on a scientific review of previous studies in both international and Bulgarian contexts, focusing on the attitudes of lecturers and the perceptions of students from the three generations involved in the educational process. A descriptive research strategy is employed to support the thesis. A survey was conducted using a questionnaire to implement the descriptive method. With a population size of 37,403 students, the respondents formed a sample size of 662 respondents, achieving a confidence level of 99.056% and a margin of error of 3.78%. The results are presented using two-dimensional distributions in the form of cross-tabulations. The ordinal relationships between the categories of a given variable are represented using ordinal (rank) scales, applying Kendall’s tau-b and Spearman’s rank correlation coefficients. The calculations were carried out using IBM SPSS software. The study found no significant correlation between the characteristics of different generations and their preferred teaching methods. At the same time, generational traits did not influence attitudes towards acquiring new knowledge and skills during the educational process.